The Great Famine: a simple general equilibrium model - McGregor, Pat (Economic & Social Studies, 1995)
A general equilibrium model of a poor peasant economy is developed in this paper, one where subsistence is the major concern of many and the absence of a capital market leads to the production possibilities of each agent being constrained by his current resources. A famine situation is then characterised by a wage rate that is below subsistence though the wage-rent ratio is raised. The latter explains why the Famine saw a rapid expansion in livestock production. Despite the low wage, public works facilitated the inter-temporal allocation of resources by the better-off. The government response was to reduce the wage rate so that the poor starved.
Keywords: Great Famine; Equilibrium models; Ireland; Rural economy; Economic history